2003
DOI: 10.1029/2002gl016411
|View full text |Cite
|
Sign up to set email alerts
|

Cluster electric current density measurements within a magnetic flux rope in the plasma sheet

Abstract: [1] On August 22, 2001 all 4 Cluster spacecraft nearly simultaneously penetrated a magnetic flux rope in the tail. The flux rope encounter took place in the central plasma sheet, b i $ 1 -2, near the leading edge of a bursty bulk flow. The ''time-of-flight'' of the flux rope across the 4 spacecraft yielded V x $ 700 km/s and a diameter of $1 R e . The speed at which the flux rope moved over the spacecraft is in close agreement with the Cluster plasma measurements. The magnetic field profiles measured at each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
122
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 86 publications
(139 citation statements)
references
References 21 publications
16
122
1
Order By: Relevance
“…In a previous study by Slavin et al (2003a), it was demonstrated that the magnetic field measurements of the flux ropes in the near tail can be successfully fitted with force-free flux rope models, thus suggesting that the observed flux ropes propagating towards the Earth are truly force free. This suggestion was further supported by the application of the curlometer technique to a flux rope registered by the Cluster spacecraft in the magnetotail (Slavin et al, 2003b). The analysis showed that the current in the observed flux rope is largely field aligned and although the flux ropes in the magnetotail are not strictly force free the usage of the force-free approximation proves to be reasonable.…”
Section: Analysis and Resultsmentioning
confidence: 75%
“…In a previous study by Slavin et al (2003a), it was demonstrated that the magnetic field measurements of the flux ropes in the near tail can be successfully fitted with force-free flux rope models, thus suggesting that the observed flux ropes propagating towards the Earth are truly force free. This suggestion was further supported by the application of the curlometer technique to a flux rope registered by the Cluster spacecraft in the magnetotail (Slavin et al, 2003b). The analysis showed that the current in the observed flux rope is largely field aligned and although the flux ropes in the magnetotail are not strictly force free the usage of the force-free approximation proves to be reasonable.…”
Section: Analysis and Resultsmentioning
confidence: 75%
“…Earthward moving flux ropes have also been observed by Cluster (e.g. Slavin et al, 2003b;Henderson et al, 2006), which implies that multiple X-lines may exist in the tail within 20 R E of the Earth.…”
Section: Introductionmentioning
confidence: 88%
“…One flux rope event on 22 August 2001 has been verified by Slavin et al [2003aSlavin et al [ , 2003b, who found that it is earthward moving and its size is about 1 R E . Figure 5 demonstrates the magnetic rotation features of this flux rope event as calculated by MRA method.…”
Section: Applicationsmentioning
confidence: 99%